2008
DOI: 10.1194/jlr.m700554-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol supply and SREBPs modulate transcription of the Niemann-Pick C-1 gene in steroidogenic tissues

Abstract: We tested whether sterol-regulatory element binding proteins (SREBPs) mediate sterol-regulated transactivation of the Niemann-Pick C-1 (NPC-1) gene. Loading granulosa cells with 22-or 25-hydroxycholesterol decreased NPC-1 mRNA, whereas culturing in cholesterol-depleted medium or inhibition of cholesterol biosynthesis increased NPC-1 promoter activity and NPC-1 mRNA abundance. Cotransfection of SREBP1a, SREBP1c, and SREBP2 and the NPC-1 promoter-luciferase reporter into granulosa cell lines increased the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The expression level of NPC1 was reduced in cholesterol-replete placentas, as demonstrated in other tissues (70), and as such would not enhance transport from lysosomes. Though the mechanism of regulation is thought to be via SREBP-2, a different regulatory mechanism exists in the rapidly growing placenta since SREBP-2 levels are not affected significantly in the cholesterol-replete placenta (54).…”
Section: Placentamentioning
confidence: 82%
“…The expression level of NPC1 was reduced in cholesterol-replete placentas, as demonstrated in other tissues (70), and as such would not enhance transport from lysosomes. Though the mechanism of regulation is thought to be via SREBP-2, a different regulatory mechanism exists in the rapidly growing placenta since SREBP-2 levels are not affected significantly in the cholesterol-replete placenta (54).…”
Section: Placentamentioning
confidence: 82%
“…The increased expression of HMGR in the SCARB1 Ϫ / Ϫ ovary was interpreted to be an intracellular feedback response to the reduction in intracellular cholesterol in the transgenic ovaries ( 31 ). The mouse bearing spontaneous mutation in the Niemann-Pick C1 gene is unable to process LDL cholesterol but displays circulating progesterone concentrations that do not differ from WT mice ( 32 ).…”
Section: Downloaded Frommentioning
confidence: 99%
“…As all three sources were believed to have been compromised in the present study, it must be concluded that cholesterol stored in the CL in the form of cholestryl esters was the source of the substrate for progesterone synthesis. The feedback system for cholesterol homeostasis is regulated by the abundance of the transcriptionally active form of sterol-regulatory element binding protein (SREBP) ( 31 ). An important transcriptional target of SREBP is the liver alone ( 13 ).…”
Section: Downloaded Frommentioning
confidence: 99%
“…However, subsequent studies performed in vitro using human fibroblasts, mouse fibroblasts, and porcine granulosa cells indicated that the NPC1 or Npc1 gene is downregulated at the transcriptional level by feedback inhibition of the sterol regulatory element-binding protein (SREBP) pathway (20,21). These studies also indicated that the NPC1 or Npc1 gene promoter region in humans, mice, and pigs possesses both sterol regulatory element (SRE)-like sequences and classic SRE sequences and is therefore capable of interacting with all 3 forms of mature (m)-SREBP proteins to regulate transcription of the NPC1 or Npc1 gene.…”
Section: Introductionmentioning
confidence: 98%